Taxation and multinational enterprise - Chown, John F. (London : Longman, 1974)
This book is intended to examines the problem associated with the taxation of multinational businesses with inclusion of other clime.
Label mounted on fly leaf: Longman, Inc., New York.
Includes bibliographical references and index.
ne 24/01/2019
Loans
Keywords: International business enterprises